Pengaruh Pemberian Ekstrak Etlingera hemisphaerica terhadap HDL dan LDL pada Mus musculus - Athika Ulfah Putri; Aceng Ruyani; Euis Nursa’adah; Endang Widi Winarni; Rendy Wikrama Wardana (Universitas PGRI Silampari, 2024)
The aim of this study was to test the ethanol extract of Hongje fruit (Etlingera hemisphaerica) in regulating High Density Lipoprotein (HDL) and Low Density Lipoprotein (LDL) levels in mice (Mus musculus). HDL and LDL levels were measured using four treatment groups (one control, two doses of EEBE, and one dose of simvastatin), with each group with five M. musculus replicates whose pathological conditions were induced by a high-fat diet for 10 days. The extract given consisted of two doses of EEBE, namely (0.26 and 0.39) mg/dl Body Weight (BW) and a comparison dose (simvastatin 0.52 mg/dL BW). Data collection was carried out over a period of 13 days before and after EEBE grant. Based on the BNT test, the average HDL treatment level in the treatment group increased at the EEBE dose (0.39mg/g BW), namely before treatment the HDL level was 39.3 mg/dL and after treatment the HDL level was 41.8mg/dL by 6. 20%. Meanwhile, LDL in the treatment group experienced a decrease at the EEBE dose (0.39 mg/g BW), namely before treatment it was 145.2 mg/dL and after treatment it became 140.8 mg/dL by -3.30%.